Rezension von: Richert, Fritz, Karl Adler - Bienert, Hans-Dieter (Württembergisch Franken, 1994)
Fritz Richert, Karl Adler. Musiker, Verfolgter, Helfer. Ein Lebensbild (Veröffentlichungen des Archivs der Stadt Stuttgart 46), Stuttgart (Klett-Cotta) 1990. 88 S., 31 Abb.